Prospective randomised control study of dexmedetomidine for controlled hypotension in functional endoscopic sinus surgery - K., Mahendran; Priya, Rasika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Functional endoscopic sinus surgery is one of the commonly performed Surgeries. Induced hypotension is a method employed in functional endoscopic sinus surgery to reduce blood loss and to improve the visibility of the surgical field. This study aimed to evaluate the effect of dexmedetomidine infusion on the requirement of Isoflurane to produce controlled hypotension (mean arterial pressure of 60-70 mmHg), quality of the bloodless surgical field, duration of surgery, and the awakening time in patients undergoing Functional endoscopic sinus surgery (FESS). Methods: 50 patients were divided into Group D, Group C Group D. After successful tracheal intubation, anesthesia was maintained with 66% nitrous oxide + 33% oxygen + isoflurane titrated to achieve a mean arterial pressure (MAP) of 60-70 mmHg. Isoflurane and dexmedetomidine/saline infusion was stopped 10-15 minutes before the end of surgery. The intraoperative surgical field was assessed by using a 6 points Fromme-Boezaart scale. Results: A statistically significant (p<0.001) reduction in intraoperative isoflurane requirement in patients receiving dexmedetomidine infusion (0.387±0.102) in comparison to those receiving placebo (1.7±0.211). Both the group provided better visualization of the surgical field. The duration of surgery was statistically (p=0.004) low in Group D (76.84±14.174) compared to group C (94.1±25.083). The awakening time in min was statistically (p=0.001) low in group D (5.12±1.691) compared to group C (9.72±1.100). Conclusions: Dexmedetomidine infusion helps in achieving a targeted reduction in MAP reduced intraoperative Isoflurane requirement, better bloodless field, and faster awakening in patients undergoing Functional endoscopic sinus surgery.